The graduated insertion of Pronatec technical courses in the labor market - André Luis Gonçalves Pereira; Ramon de Oliveira (Universidade Federal de Santa Catarina, 2019)
Pronatec has established itself as one of the largest professional qualification programs developed by the Federal Government. It is considered not only the number of qualified people, but also the financial resources available and the involvement of several institutional agents, whether public or private. So, this article discusses the repercussions of the activities in this Program on the young people lives who seek these formations as mechanisms to help their insertion into the labor market. The courses that served as reference for this analysis were those of Food Technician and Work Safety Technician, held at the Campus of the Federal Institute of Pernambuco (IFPE), in Vitória de Santo Antão, in the countryside of Pernambuco state. Interviews were conducted with 12 graduates (six from each technical course investigated), 03 teachers and 02 Pronatec managers at the Vitória de Santo Antão Campus. The results showed that Pronatec has offered a predominance of short-term and disconnected courses from any perspective of omnilateral formation configured as a mechanism for the student's instrumentation for a hypothetical future work, strengthening common sense, reinforcing the meritocratic vision that serves to criminalization of poverty and, above all, to create the illusion that education transforms individual lives individually.